Caracterização de cimento odontológico obtido a partir de um vidro preparado pelo método dos precursores poliméricos - Bertolini, Marcio José [UNESP]; Zaghete, Maria Aparecida [UNESP]; Gimenes, Rossano [UNESP]; Paiva-Santos, Carlos de Oliveira [UNESP]; Palma-Dibb, Regina Guenka (Sociedade Brasileira de Química, 2005)
Glass ionomer cements are glass and polymer composite materials. These materials currently find use in dentistry. The purpose of this work is to obtain glass powders based on the composition 4.5SiO2 - 3Al2O3 - 2CaO to be used in dentistry. The powders were prepared by a chemical route at 700 0C. The properties of glass ionomer cements obtained from powders prepared at 700 ºC were studied. Diametral tensile strength and microhardness were evaluated for the experimental glass ionomer cements and a commercial material. It was concluded that the properties of experimental cements were similar to those of the commercial ones.
Characterization of dental cement obtained from a glass prepared by the polymeric precursor method
Keywords: cements; dental; glass